REKONSTRUKSI IKLIM DAN LINGKUNGAN PENGENDAPAN KALA PLIOSEN AKHIR-PLISTOSEN DI BEBERAPA DAERAH PULAU JAWA BERDASARKAN PALINOSTRATIGRAFI DAN PALINOFASIES. - Kurniadi, Dedy
Palynofacies study in a general way is to mean all organic matter/palynology that is recovered from a sediment by the standard palynological processing technique (Batten and Stead, 2005). Result from palynofacies analysis can be used to reconstruct climate and depositional environment in several location in Java Island during Late Pliocene-Pleistocene. Location 1 of Cibanyawak River section, Sumedang, West Java, Location 2 is Cisaat River section, Bumiayu, Central Java and Location 3 is Perning-Lakardowo section, Mojokerto, East Java. The palynofacies or palynological materials from sediment could be grouped based on some parameters: Percentage of Amorphous Organic Matters /AOM, Percentage of Phytoclasts, Percentage of Palynomorphs, Opaque : Translucents Phytoclast Ratio (O:TR), Opaque equidimentional : Opaque lath Phytoclast Ratio (O-Eq:O-La) and Palynological Marine Index (PMI). In Location 1 found the Late Pliocene marine sediments of Kaliwangu Formation which indicated by the appereance of Stenochlaenidites papuanus and Dacrycarpidites australiensis and Pleistocene sediments (mangrove and backmangrove) of Citalang Formation which deposited in fluvial depositional environment. This section shows 4 climate changes from older to younger: ColdWet, Warm-Wet, Cold-Dry, Warm-Wet and Cold-Wet. Location 2 had Late Pliocene marine sediments of Kalibiuk formation and Pleistocene transition to fluvial sediments of Kaliglagah Formation, middle part of the section interpreted as mangrove and backmangrove environment while freshwater swamp occured in the top of the section. The age boundary defined by last appereance of Stenochlaenidites papuanus. This section has five climate changes from older to younger: Cold-Wet, Warm-Wet, Cold-Dry, Warm-Wet and Cold-Dry. The Late Pliocene marine sediments (Inner Neritic) of Lower Pucangan Formation while Upper Pucangan Formation interpreted as deltafront-deltaplain environment and Pleistocene transition to fluvial sediments of Kabuh Formation have been found in the Location 3 with 6 times climate changes from older to younger: Warm-Wet, Cold-Wet, Warm-Dry, Cold-Dry, Warm-Wet and Cold-Dry. Based on several classification (Pucknall dan Beegs 1990, Fenton, 1984 dan Tyson, 1995), Palinofacies environment of the study areas could be devided into: Location 1: marginal dysosic-anoxic basin Location 2: highly proximal basin and marginal dysosic-anoxic basin. Location 3: highly proximal basin and marginal dysosic-anoxic basin.